Leaf-vein-inspired multi-organ microfluidic chip for modeling breast cancer CTC organotropism - Liuyin Liu; Xiaoli Qu; Zhe Wang; Cheng Ji; Rui Ling; Changjiao Yan (Frontiers in Oncology)
ObjectiveBreast cancer is characterized by a high tendency for organ-specific metastasis. This study aims to develop a multi-organ metastasis model for circulating tumor cells (CTCs) of breast cancer to explore their organotropism in common target organs, including the liver, bone, and lung.MethodsWe fabricated a biomimetic microfluidic organ-on-a-chip inspired by leaf veins. In this system, three-dimensional cultures of human hepatocyte LO2 cells, human bone marrow-derived mesenchymal stem cells, and human fetal lung fibroblast 1 cells were established in separate chambers to mimic liver, bone, and lung microenvironments, respectively. Then, various breast cancer subtypes (MCF-7, SKBR3, MDA-MB-231) were perfused through the system. We quantified their invasive cell numbers and organ-specific localization in each organ. Further, MDA-MB-231 cells overexpressing metastasis-related genes (CXCR4, claudin-2, Linc-ZNF469-3) were tested. Additionally, the integration of tumor organoids with microfluidic chips was employed to evaluate the predictive capacity of this model for patient-specific metastatic patterns.ResultsThere are significant differences in the number of invasive cells and organ-specific localization among different breast cancer subtypes in each organ. MCF-7 cells show the highest invasion and most prominent localization in bone; SKBR3 cells in liver and lung. MDA-MB-231 cells have no obvious difference in organotropism among the three organs, but their invasive numbers are higher than those of MCF-7 cells. CXCR4-OE, claudin-2-OE, and Linc-ZNF469-3-OE MDA-MB-231 cells demonstrate the highest invasion and most prominent localization in bone, liver, and lung respectively. Organoid cells derived from a breast cancer patient with pulmonary metastasis at initial diagnosis, when perfused into the system, selectively invaded the lung organ, but did not invade the liver, bone, or control pores.ConclusionThis leaf-vein-inspired multi-organ microfluidic chip demonstrates significant application value for studying breast cancer CTC organotropism and serves as a powerful predictive tool for early warning of high-risk organ metastasis.